(untitled) (Biological Sciences - PJSIR, 2004)
5, 6, 7, 3’, 4’-Pentamethoxyflavone (8) isolated from the leaves of Orthosiphon stamineus has been synthesized by following an unambiguous route. All the new products have been characterised on the basis of spectral data and microanalysis.